PROTEST AND THE AMBIGUOUS POLITICS OF INDIGNATION an empirical and conceptual study of mobilizing... emotions. - Knops, Louise (Mobilization series on social movements, protest, and culture., 2025)
"What makes indignation 'political'? And why should we care about it? Drawing on field-work among four movements in Belgium (2017-2021) - The Youth for Climate movement, the Citizen platform for refugee support, the Yellow Vests movement and the radical-right movement Schild & Vrienden - this book investigates both the meanings and implications of indignation in the context of mobilization. In particular, the book argues that what is often reduced to a form of 'moral anger' which triggers protest is in fact much more complex and ambiguous. Indignation is not just anger: it is rooted in hate and love. It may also harbour textures of compassion and disgust. It may be a culmination of resentful feelings or a reaction to fear. In some contentious contexts, it displays a distinctive righteous connotation; in others, it is rooted in historical forms of injustice and discrimination. It triggers some of the most disruptive forms of contention, while also reinforcing hegemonic norms and beliefs. Indignation, overall, is both one of the most explicitly political affects of mobilization, while also reinforcing broader trends of depoliticization. By unveiling the affective complexity of indignation, the author shows the multiple ways in which the indignation expressed by social movements both politicizes and depoliticizes, and what this means for the role played by emotions and affects in today's landscape of conflictuality"--